Analisis Implementasi SAK EMKM Terhadap Keandalan Penyajian Laporan Keuangan Pada Usaha Mikro, Kecil, dan Menengah - Deby Agustin; Desty Nurulaini; Dewi D; Salma Afni Ladytanesia Herdian (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting Indonesia’s economic growth by creating employment opportunities and contributing to regional and national development. However, many MSMEs still experience difficulties in preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), resulting in financial information that is less reliable and less useful for decision-making. This study aims to analyze the implementation of SAK EMKM in MSMEs, examine the reliability of financial statement presentation, and determine the effect of SAK EMKM implementation on the reliability of financial reporting. The study employs a quantitative approach with descriptive and associative research designs. Data will be collected through questionnaires distributed to culinary MSME owners in Bandung Regency using purposive sampling. The data will be analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression, t-tests, and the coefficient of determination with SPSS software. The expected findings indicate that the implementation of SAK EMKM has a positive effect on the reliability of financial statement presentation. The results are expected to provide valuable insights for MSME owners, academics, and policymakers in improving financial reporting quality and strengthening the implementation of accounting standards among MSMEs.